1992
DOI: 10.1063/1.462956
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics at the glass transition: One dimensional and two dimensional nuclear magnetic resonance studies of a glass-forming discotic liquid crystal

Abstract: The molecular dynamics of the aromatic core as well as the hydrocarbon side chains have been studied in a new kind of glass-forming discotic liquid crystal, based on a triphenylene core. It serves as a model compound in which only a limited number of degrees of freedom is activated at the glass transition. Slow motion with non-Arrhenius temperature dependence (α process) is associated with the axial motion of the discs around the column axis. The geometry of this rotation is found to be neither a simple threef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…In the case of the HBC derivatives, 1 H spectra do not only provide clear evidence for the presence of a LC phase, they also allow the persistence of the columnar packing as well as the underlying processes of molecular rotations to be identified (18,19,20). In contrast to previous NMR investigations performed on this class of materials (69,55), all the results presented here are directly obtainable from as-synthesized samples, requiring experimental times on the order of a few hours, so that 1 H MAS methods are particularly well suited to routine spectroscopic investigations in the course of the synthesis of solid-state materials.…”
Section: Molecular Motions In Liquid-crystalline Phasesmentioning
confidence: 79%
“…In the case of the HBC derivatives, 1 H spectra do not only provide clear evidence for the presence of a LC phase, they also allow the persistence of the columnar packing as well as the underlying processes of molecular rotations to be identified (18,19,20). In contrast to previous NMR investigations performed on this class of materials (69,55), all the results presented here are directly obtainable from as-synthesized samples, requiring experimental times on the order of a few hours, so that 1 H MAS methods are particularly well suited to routine spectroscopic investigations in the course of the synthesis of solid-state materials.…”
Section: Molecular Motions In Liquid-crystalline Phasesmentioning
confidence: 79%
“…They are known to increase the temperature range of discotic columnar mesophases [39], and disc-shaped aromatic molecules that do not form columnar mesophases on their own may display columnar liquid crystalline phases when linked together. Oligomers do not crystallize on cooling but rather form an anisotropic glass of the preceding mesophase structure [40]. Finally, the oligomeric approach provides a wide flexibility in molecular design.…”
Section: Alignment Of Oligomeric Dlcsmentioning
confidence: 99%
“…Apart from their relevance for novel functional materials, DLC have also attracted attention as an interesting, low-dimensional glass-forming system [5,6]. Since glass formation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of their high degree of positional order in the plastic crystal phase, these systems show a temperature dependent primary relaxation time that obeys the Vogel-Fulcher-Tamman (VFT) law which is characteristic for glass forming systems [7][8][9]. 2 H NMR and dielectric spectroscopy studies on triphenylene derivatives revealed that the glass transition is related to the hindered rotation of rotationally disordered discs around their columnar axis and is not coupled with the side chain mobility [5,10,11]. For another hexasubstituted triphenylene derivative, where one of the side chains is a chloroester, it was found that the glass transition is highly anisotropic, having a much more pronounced effect along the columnar axis [6].…”
Section: Introductionmentioning
confidence: 99%